Teaching strategies for the simulation of Basic Life Support in Nursing: An integrative review (Research, Society and Development, 2021)
Objective: to analyze the contribution of the use of clinical simulation as a strategy for teaching and learning Basic Life Support in Undergraduate Nursing. Method: integrative review of 16 full articles, available in LILACS, PubMed Central, SCOPUS, CINAHL, Web of Science, Embase, Cochrane and Scielo databases. Results: of the evaluated articles, the majority originated from quasi-experimental researches (43.75%), were developed in Brazil (43.75%), with teaching-learning strategies involving simulations with robotics (with high and medium fidelity simulators), Role Play, lectures, online game, online course, Objective Structured Clinical Examination (OSCE), scenic simulations (with standardized patients), Problem Based Learning (PBL) and the Active Learning Model for Critical Thinking (ALMCT). The use of these strategies shows better learning, development of psychomotor skills, self-confidence, security and teamwork in students. Conclusion: clinical simulation in Basic Life Support presents better recognition of cardiorespiratory arrest, effective chest compressions, early defibrillation, development of advanced clinical management skills, including teamwork and decision-making skills.